A Case of Retinal Artery Macroaneurysm: A Ticking Time Bomb of the Eye - Parajuli, Sanket; Sharma, Sadhana; Sharma, Ruchi (Nepal Medical College Journal, 2023)
Retinal arterial macroaneurysms are acquired, focal dilation of a retinal artery. Patients with retinal arterial macroaneurysms can present with an acute or gradual loss of vision as a result of vitreous hemorrhage, preretinal hemorrhage or macular edema. An 81 year old female, a known hypertensive since 12 years under regular follow-up visits, presented to us with vitreous hemorrhage secondary to ruptured retinal artery macroaneurysm in the right eye. She was managed with indirect argon laser treatment. Accurate diagnosis and co-management are crucial to save vision and help prevent life altering complications. This case report emphasizes the need of ocular examination in systemic diseases and further establishes ‘eye as the window of the body’.